EXPLORING STUDENTS’ CONCEPTUAL AND PROCEDURAL ERRORS IN AKM-BASED CENTRAL TENDENCY TASKS - Haryati, Hamida; sukirwan, Sukirwan; Muhtadi, Dedi (Journal of Authentic Research on Mathematics Education (JARME), 2026)
This study investigates students’ errors in solving Asesmen Kompetensi Minimum (AKM)-based problems on measures of central tendency, with a focus on conceptual understanding, procedural reasoning, and technical accuracy. Employing a qualitative descriptive design, data were collected from 20 eighth-grade students through an AKM-based diagnostic test and semi-structured interviews. The findings reveal that students’ errors are predominantly conceptual and procedural, particularly in interpreting the meaning of mean and median, planning solution strategies, and systematically analyzing contextual data representations. Technical errors occurred less frequently and were mainly associated with computational inaccuracy and limited reflective checking. These results indicate that students’ engagement with AKM-style statistics tasks is characterized by surface-level processing rather than meaningful statistical reasoning. The study contributes to research on statistical literacy by highlighting the need to integrate conceptual understanding, procedural planning, and reflective practices in numeracy instruction. Implications are discussed for strengthening assessment-oriented learning and supporting students’ numeracy development within competency-based curricula.